(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article analyzes Jack Gelber’s The Connection, first produced in 1959, at the Living Theatre, where it became an Off-Broadway cultural phenomenon. By using the play-within-the-play device, it combines the unabashed presentation of a group of heroin addicts’ anticipation for the arrival of their dealer with the dramatizing process of the narcotics users’ routine. Through the study of The Connection’s metatheatrical structure, and its ambiguous defiance of several formal and thematic tendencies seen in the coetaneous American mainstream arts, I argue that its greatest singularity lies in its deliberate effort to bore audiences.